Level of Knowledge, Attitudes, and Skills of Farmers towards SIPINDO Application in Subur Makmur Farmers Group Baran Village - Dwilatifa, Aini Zahra; Mariyono, Joko; Setiyawan, Hery (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The SIPINDO (Indonesian Agricultural Information System) application was a digital platform designed to assist farmers in obtaining agricultural information. This study aimed to describe farmers’ knowledge, attitudes, and skills toward the SIPINDO application and to analyze the impact of the SIPINDO application intervention within the Subur Makmur Farmer Group. The research method employed an experimental approach using a true-experimental design with a pre-test and post-test group design. The data analysis methods included descriptive analysis and the Paired Sample t-Test. The results of the study indicated that, after the intervention, farmers in the Subur Makmur Farmer Group demonstrated higher levels of knowledge, attitudes, and skills. The pre-test results for the knowledge variable showed that the majority of farmers were in the moderate category, totaling 30 individuals or 60%, while 12 individuals were in the low category and only 8 individuals were in the high category. The post-test results showed that the number in the low category decreased to 3 individuals, the moderate category decreased to 17 individuals, and the high category increased to 30 individuals or 60%. In terms of the attitude variable, the pre-test results showed that most farmers were in the moderate category, totaling 30 individuals or 60%, while 7 individuals were in the low category and 13 in the high category. After the intervention, the post-test results revealed an increase in the number of farmers in the high category to 22 individuals or 44%. For the skills variable, the pre-test indicated that the majority of farmers were in the low category, with 26 individuals or 52%. Following the intervention, the post-test results showed that the number of farmers in the low category decreased to 4 individuals, while those in the high category increased by 24 individuals. The increase in the high category across all three variables indicated that the intervention provided through the SIPINDO application was effective in improving farmers’ behavior and engagement with the application in the Subur Makmur Farmer Group, Baran Village.